Sirvydas ar Širvydas? - Zinkevičius, Zigmas (Baltistica, 1981)
Sirvydas or Širvydas? The surname of one of the most noted creators of old Lithuanian writing and the first Lithuanian lexicographer is used in Lithuanian in two variants – Sirvydas and Širvydas. By referring to the data of archives and the data of present-day personal names the author arrives at the conclusion that the true name of the scholar is Sirvydas, while Širvydas is the polonized version of the former. Therefore one should use the authentic form of the surname, viz. Sirvydas.